Was the Supernova of 1054 CE Recorded in Constantinople? A Historical and Astronomical Reassessment - Murata, Koji; Hayakawa, Hisashi (De Medio Aevo, 2024)
This paper critically reexamines two candidate records of the supernova of 1054 CE (SN 1054) that allegedly came from Constantinople, integrating historical and astronomical analyses. East Asian records documented SN 1054 in detail and formed the basis for astronomical discussions. In contrast, few reports of SN 1054 from Western Eurasia (Europe and West Asia) are known. The majority of such alleged reports have been rejected on the basis of philological and astronomical discussions. This study scrutinizes two potential accounts of SN 1054. The first is Ibn Buṭlān’s account, as cited in a later work. The second is a specific class of Byzantine gold coin issued in Constantinople, which may have commemorated SN 1054. Our reanalysis of Ibn Buṭlān’s record questions its connection to Constantinople. We also challenge speculation regarding the Byzantine coin, analysing contemporary historical and numismatic backgrounds. The paper also compares these accounts with the reconstructed SN light curve and modern astronomical calculations to assess the astronomical aspect of these records.